A comparative analysis of energy dissipation and equivalent viscous damping of RC columns subjected to uniaxial and biaxial loading - Hugo Rodrigues (2012)
The hysteretic behaviour of RC columns has been object of many experimental studies over the past years. However, the majority of these studies are focused on unidirectional loading. An experimental program was carried out where 24 columns were tested for different loading histories, under uniaxial and biaxial conditions. The experimental results are presented in this paper and are discussed in terms of global column behaviour, and particularly with regards to energy dissipation and damping capacity. The energy dissipation capacity of the columns was evaluated in terms of cumulative dissipated energy, comparing uniaxial and biaxial test results, and individual cycle dissipated energy. Ultimately, an equation relating the normalised dissipated energy with the displacement ductility is proposed. The equivalent viscous damping was analysed by comparing the uniaxial with biaxial test results, demonstrating the high influence of the load path in the biaxial response of RC columns. Proposals for estimating the equivalent viscous damping given by other authors are compared with the experimental results. Finally, simplified expressions are proposed to estimate equivalent viscous damping in RC columns under biaxial loading.